Community-engaged greening: understanding the role of community engagement in vacant lot greening initiatives - Campbell, Stephanie (Kansas State University, 2023)
Due to a history of decentralization, urban vacancy is an issue plaguing many cities today (G. Kim et al., 2020). Recently, communities have started to investigate urban greening as a management technique to lessen the detrimental effects of vacancy (Heckert and Mennis, 2012). In order to address the issue of urban vacant land and promote long-term regeneration through urban greening initiatives, community engagement is a critical component (G. Kim et al., 2020). Research indicates that community engagement can help diverse resident populations better articulate their needs and formulate a vision, thus helping to reduce the risk of the negative consequences of urban greening, such as gentrification (Campbell and Lindquist, 2021). However, it is unclear how the components and dimensions of the community engagement process and its results support urban greening efforts, especially in high vacancy areas. There is also a need for strategies, guidance, and policies to govern how we design spaces, such as vacant lots. This study aims to explore the role community engagement has in the implementation of greening vacant lots initiatives. Through exploring precedent studies, this study examines greening vacant lot initiatives in several cities to understand the greening programs and community engagement processes. Semi structured interviews with project coordinators were conducted to gain insight into the community engagement process. The study focuses on the greening of vacant lots as informal spaces, to help understand the role of community engagement in repurposing such spaces. Vacant lots in Kansas City, Missouri have served as an example of how these strategies and principles can be applied. The outcome of this research is a set of strategies and principles to help guide the community-engaged greening of vacant land. Findings highlight the importance of community engagement and community led approaches in the success of greening vacant lot initiatives. Findings also indicate the importance of communication, tailoring the process to the community, and practicing active engagements. Core values such as building trust, being understanding and empathetic, being transparent, and being flexible were also determined. The strategies and principles developed from this research can help guide future greening initiatives and help foster meaningful and effective community engagement.
Keywords: Community engagement; Greening; Vacant lots; Urban vacancy; Urban green space